Assessing public knowledge, attitudes and determinants of third COVID-19 vaccine booster dose acceptance: current scenario and future perspectives - Ammar Abdulrahman Jairoun; Sabaa Saleh Al-Hemyari; Faris El-Dahiyat; Maimona Jairoun; Moyad Shahwan; Mena Al Ani; Mustafa Habeb; Zaheer- (Taylor & Francis Group, 2022)
Background People with weakened immune systems may not develop adequate protection after taking two doses of the mRNA-combined COVID-19 vaccine. The additional dose may improve the level of protection against Covid-19. Objectives Current study aimed to evaluate the knowledge, attitude and determents of third COVID-19 vaccine booster dose acceptance among population in the UAE. Methods and materials This is online descriptive cross-sectional community-based study conducted among the students and faculty of Ajman University from 25 August to 20 October 2021. The questionnaire, which was in the English language, encompassed two sections containing 22 items. Section one gathered the demographic details of the respondents, while Section two used 13 questions to evaluate the respondents' knowledge of and attitude to the third COVID-19 vaccine booster dose. Results 614 respondents participated in this study. The average knowledge score was 44.6% with a 95% confidence interval (CI) of [41%, 49%]. Better knowledge scores were observed in postgraduates (OR 4.29; 95% CI 2.28-8.11), employees in the healthcare sector (OR 1.62; 95% CI 1.05-2.51), participants who had relatives infected with the Covid-19 (OR 1.46; 95% CI 1.05-2.02), participants who had infected with Covid-19 (OR 2.21; 95% CI 1.43-3.43) and participants who had received first two doses of the COVID-19 vaccine (OR 2.08; 95% CI 1.40-3.11). The average attitude score was 70.2% with a 95% confidence interval (CI) of [69.2%, 71.2%]. Conclusion Necessary steps should be taken by the government and public health authorities, in line with the local culture, to increase vaccination acceptance and foster positive attitudes towards the vaccine. A suitable approach to this would be to develop an educational framework that could demonstrate the risks of vaccine avoidance or delay to the general population. Moreover, health authorities should pay more attention to the false information being disseminated across the internet, especially social media. Also, healthcare workers should be trained in vaccinology and virology to make sure that they are able to understand important developments in these fields and convey the findings to their patients.